Carbon Exchange and Accumulation in an Orinoco High Plains Native Savanna Ecosystem as Measured by Eddy Covariance - Morales-Rincon, Luis A.; Hernandez, Andrea J.; Rodriguez-Hernandez, Nubia S.; Jimenez, Rodrigo (Frontiers in Environmental Science, 2021)
Savanna ecosystems cover ~20% of the total land surface and account for ~30% of the terrestrial global net primary production. They are also highly sensitive to climate change, since their carbon sink capacity may decline under rising temperatures and irregular rainfall. These responses, which will define the future climate role of the savanna ecosystems, are currently not well understood. The Colombian Orinoco River basin (“Llanos”) natural savannas are being rapidly converted to agriculture. This clearly causes biodiversity loss. The impact of this transformation on carbon fluxes and accumulation is much less clear. It is thus urgent to understand the Llanos natural savanna ecosystem services, including the carbon cycle and underlying mechanisms. Here we report and analyze 2 years of measurements of carbon dioxide fluxes from a restored (natural but secondary) Llanos High Plains savanna ecosystem, using eddy covariance. Meteorological conditions, particularly rainfall, were quite variable during the measurement period. During the first year of measurements, the savanna was a weak carbon source (35 gC∙m-2), while during the second year, the system was a strong carbon sink (-273 gC∙m-2), despite receiving less rainfall than during the first year. As expected, the savanna net ecosystem exchange (NEE) was highly dependent on global solar radiation, soil water content, and ecosystem respiration. We found that after ~10 days of nominal drought, i.e. with less than ~5 mm/day precipitation, the NEE became highly dependent on the drought duration. The ecosystem reached a critical condition of low activity after ~60 days of nominal drought. Based on these findings, we developed and applied a simple standard meteorologically-based model that properly reproduced the observations. Our results imply that perturbations in the precipitation cycle might generate major changes in carbon fluxes and accumulation in llanos’ savannas.